Edukasi Upaya Pencegahan Gangguan Kesehatan Mata di SD Negeri Pancur, Kota Serang, Banten - Muhammad Alyf Romadon; Alvinarose Febri Hardiwijaya; Wulan Shaumi Fadhilati; Yusep Gunawan; Mila Ermila Hendriyani (University of Muhammadiyah Sumatera Utara, 2023)
Education in efforts to prevent eye health problems as a form of community service. The socialization was carried out at SDN Pancur, Serang City with the theme